School Physical Education Program Impact on Psychological Well-Being and Cognitive Ability of Primary School Children - Kliziene, Irina; Emeljanovas, Arunas; Dubosas, Mindaugas (Physical Education Theory and Methodology, 2023)
Study purpose. This study aimed to determine the impact of school Physical Education programs on well-being and cognitive ability (CA), as measured by mathematics achievements, in primary school children. Materials and methods. The study participants selected from three schools were 100 girls and 102 boys aged 9–10 years. According to Kliziene et al. (2022), the CA diagnostic test for mathematics in Grade 4 is grounded in Feuerstein and Lewin-Benham’s (2012) dynamic cognitive modality assessment theory, as well as the General Curriculum for Primary Education approved by the Minister of Education and Science of Lithuania (ISAK-2433, 2008). This test designed for learners in Grade 4 encompasses mathematics. The study aimed to assess the level of enthusiastic well-being by examining three primary dimensions: somatic anxiety, personal anxiety, and social anxiety. To measure anxiety, the Revised Children’s Manifest Anxiety Scale (RCMAS) was used, which consists of 37 items, with 28 of them assessing anxiety and the other 9 measuring the child’s defensiveness. In this study, a pre-/post-test experimental methodology was used to avoid any interruption of educational activities, due to the random selection of children in each group. The methodology depended on dynamic exercise, intense repetition of motor skills, differentiation, seating and parking reduction and physical activity distribution in the classroom model. Results. The CA diagnostic test was analyzed in terms of the learners’ levels of achievement (satisfactory, basic, advanced) and cognitive functions. The systematic exploration function was used to achieve systematic, non-impulsive, planned behavior when collecting data or checking information. There was a strong difference between students at the satisfactory and advanced levels in the ability to orient themselves in space and follow directions (score for boys, Post-test 2.53 (0.25) points; for girls, Post-test 2.91 (0.32) points out of a maximum 4 points; p<0.05). After the school PE program, the personality anxiety results decreased for both boys (2.68 ± 0.98 points) and girls (3.41 ± 0.55 points) (F = 4.98, p < 0.05, P = 0.729). Conclusions. Overall, the physical education program implemented in this study was found to have a positive effect on the psychological well-being of 9–10-year-old children, specifically in reducing somatic anxiety, personality anxiety, and social anxiety. Additionally, it was observed that the program led to statistically significant improvements in the children’s cognitive abilities across nine functions, including spatial orientation, sequencing, recognition of relationships and patterns, and information processing.